Pengaruh Iklim Sekolah Dan Kedisiplinan Terhadap Prestasi Belajar Siswa - Salma, Salma (Pascasarjana Universitas Negeri Makassar, 2013)
The study aims to examining, school climat, student discipline toward learning achievement in classes XI Students at Public Vocational School (SMKN) 1 Jeneponto. This type of the study a descriptive research, which categorized as quantitative research. The quantitative is meant to test hypotheses and operation of variable. The variables consists of three variables : namely school climate (X1) students discipline (X2), as independent variable, and student achievement as the dependent variable.The population of the study was grade XI at SMKN Jeneponto academic year 2011/2012 whit the total number 420 students. The samples were selected by using simple random sampling which obtained 126 students. Data were collected trough questionnaire and documentation. Data were then analyzed by employing descriptive statistic and inferential statistics. The results of the study reveal that school climate is categorized as medium, students’ discipline of grade XI at SMK 1 Jeneponto is categorized as high, the and students’ learning achievement is categorized as fair. Other than school climate, student discipline gives influence toward students learning, achievement both individually and collaboratively.